GREEN MARKETING AS A FACTOR OF SUSTAINABLE RURAL TOURISM IN THE ĐURĐEVIĆA TARA NATIONAL PARK - Bojana Ostojić; Dejan Sekulić; Andrej Mićović (Ekonomika Poljoprivrede (1979))
This paper examines the role of green marketing in developing sustainable rural tourism, with Đurđevića Tara National Park as a case study. The aim was to assess how tourism stakeholders apply green marketing principles and how tourists perceive ecological aspects of the destination. The research identified two related but distinct dimensions linking perceptions of green marketing with sustainable rural development. Correlation and regression analyses confirmed statistically significant positive relationships between these variables. Key sustainability factors include cooperation with the local community and the use of renewable energy. A moderating effect of tourists’ origin was observed: domestic tourists value education and nature preservation more, while international visitors prioritize economic and social benefits. These insights emphasize the need for an integrated approach to planning and the importance of adapting strategies to different visitor profiles to achieve long-term sustainability.